pysisyphus: Exploring potential energy surfaces in ground and excited states - Steinmetzer, Johannes; Kupfer, Stephan; Gräfe, Stefanie (International Journal of Quantum Chemistry, 2021)
Predicting the energetics of chemical transformations requires localizing stationary points on a potential energy surface. While educts and products of a chemical reaction may be known, transition state optimization is challenging as good guesses may be unavailable. Extending stationary point searches to the excited state leads to additional difficulties as several states may be close in energy, requiring efficient state tracking. Here, we report the implementation of pysisyphus, an external optimizer, that allows localization of stationary points not only in the ground state but also for excited state by providing several state-tracking algorithms. pysisyphus offers all necessary tools for calculating reaction paths, starting from the optimization of the reactants, running chain-of-states methods such as the nudged elastic band or the growing string method with subsequent transition state optimization, and a concluding intrinsic reaction coordinate calculation.
CRIS-Team Scopus Importer:2023-04-20
Keywords: chain-of-states; excited state; intrinsic reaction coordinate; optimization; transition states